Results of the use of synthetic sex attractant lures for Zygaenidae in south-eastern France (Lepidoptera: Zygaenidae) - E. Drouet; T. B. Toshova; K. A. Efetov (SHILAP, 2021)
The sex attractant 2-butyl 2-dodecenoate (EFETOV-2), (2R)-butyl (7Z)-dodecenoate (R12) (a component of Illiberis rotundata sex pheromone) and a mixture with its opposite enantiomer (2S)-butyl (7Z)-dodecenoate (R12+S12, 1:1), were tested over a period of two years for studying Zygaenidae fauna in south-eastern France. As a result, eight Zygaenidae species were attracted in the vicinity of the lures, one of them in quantities never previously recorded by other methods in France.